Teamwork in rehabilitation: a study about individual and group perceptions of health workers - Queiroz, Elizabeth; Araujo, Tereza Cristina Cavalcanti Ferreira de (Paidéia (Ribeirão Preto), 2009)
A multi-professional team intervention model has been advocated in order to achieve the goal of integral assistance. To better understand this intervention model, this study aimed to identify and compare individual and group perceptions of professionals of two rehabilitation services about teamwork. Individual and group interviews were carried out with professionals from the Spinal Cord Injury and Brain Injury specialized services at the same hospital. The main results comprised: team conceptualization; identification of positive and negative mediating factors in teamwork; assessment of the decision making process; professional autonomy; and similarities and differences between the two teams. We suggest that future studies focusing on the functioning of health teams adopt the group interview procedure.